Analisis Kemampuan Panel Surya Monokristalin 150 Watt pada Arus dan Pengisian yang Dihasilkan - Salim, M Barkah; Rajabiah, Nurlaila (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2019)
The sun is a source of energy that cannot be used up. Therefore, the utilization of solar energy must be a priority. With the many types of solar panels that have been developed, researchers conducted an analysis of 150 watt monocrystalline solar panels. The purpose of this study is to know the amount of current and voltage produced by solar panels in some conditions of the sky, namely cloudy, bright cloudy, and bright. The research method used was the experiment. From the data that has been obtained, it can be found that the energy produced by solar panels during cloudy ranges from 0.6-0.8 amperes, when it is cloudy, 0.9-1.9 amperes, and when bright 2.0-3.2 amperes. The amount of electrical energy that can be produced is 8%. However, if the sunny state can produce twice that Suggestions for readers are if you want to take data to make sure the solar panels are completely exposed to the sun during data collection and in the open area. Much better if the angle is adjusted in the direction of sunlight.